2019
DOI: 10.1088/1361-648x/ab2bd1
|View full text |Cite
|
Sign up to set email alerts
|

Stability predictions of magnetic M2AX compounds

Abstract: Based on high throughput density functional theory calculations, we evaluated systematically the stability of 580 M2AX compounds. The thermodynamic, mechanical, and dynamical stability and the magnetic structure are calculated. We found 20 compounds fulfilling all three stability criteria, confirming Cr2AlC, Cr2GeC, Cr2GaC, Cr2GaN, and Mn2 GaC, which have been synthesized. The stability trends with respect to the M- and A-elements are discussed by analyzing the formation energies, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…In general, a phase is defined as thermodynamically stable when it is on the convex hull, while a non-stable or metastable phase is above the convex hull. 5,9,16,17 With such an approach, information about decomposing phases are accessible for non-or metastable phases only, while stable phases are compared to themselves, i.e., the phase is on the hull.…”
Section: Introductionmentioning
confidence: 99%
“…In general, a phase is defined as thermodynamically stable when it is on the convex hull, while a non-stable or metastable phase is above the convex hull. 5,9,16,17 With such an approach, information about decomposing phases are accessible for non-or metastable phases only, while stable phases are compared to themselves, i.e., the phase is on the hull.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations also demonstrated that Mn 2 N with functional groups O, OH and F can be half-metals with high Curie temperatures. 13 However, high-throughput density functional theory (DFT) calculations reveal that it is difficult to obtain MAX compounds with Fe, Co, and Ni, 14,15 leading to a challenge to realize magnetic MXenes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, (V 0.5 Cr 0.5 ) 3 AlC 2 was successfully synthesized by reactive HP from elemental powders, while Cr 3 AlC 2 has never been experimentally reported [79]. Similarly, Mn has been used as an alloying element for the M-site atoms in Cr 2 AlC, forming (Cr 1-x Mn x ) 2 AlC to tailor its magnetic properties, although Mn 2 AlC does not exist [80,81]. In this section, the ordered or disordered structures of M alloyed M n+1 AX n phases are presented, and the properties of MAX phase solid solutions are discussed.…”
Section: Solid Solutionsmentioning
confidence: 99%
“…(4) Magnetic properties Most existing ternary MAX phases do not show magnetic properties, yet there have been some calculations on possible magnetic MAX phases, especially those with Mn as the M element. Mn 2 AlC and Mn 2 GeC were both calculated to be magnetic in their ground states with magnetic moments of 1.86 μB and 1.80 μB per Mn atom, respectively [81]. In 2013, Ingason et al [129] was the first to report the ferromagnetic properties of Mn 2 GaC obtained from both calculations and experiments.…”
Section: ) Electrical Conductivitymentioning
confidence: 99%